Mechanics of Fatigue Crack Closure 1988
DOI: 10.1520/stp27229s
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fatigue Crack Growth Data Obtained at Different Stress Ratios

Abstract: Fatigue crack propagation tests have been carried out on three C-Mn structural steels at stress ratios between 0.67 and −4. Surface strain gage techniques have been used to determine crack-tip closure stress and an expression proposed to relate the proportion of the stress cycle for which the crack tip is actually open U to stress ratio. Satisfactory correlation of the crack propagation results for this range of stress ratios has been achieved by defining an effective stress intensity factor range as the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 2 publications
1
11
0
Order By: Relevance
“…7(a), the data at R = 0.5 are considerably separate from the other data and the effects of R-ratio on da/dN do not wholly disappear. Similar results appeared in the work of Booth and Maddox [9]. In contrast, the results in Fig.…”
Section: Crack Closure Behavioursupporting
confidence: 90%
See 1 more Smart Citation
“…7(a), the data at R = 0.5 are considerably separate from the other data and the effects of R-ratio on da/dN do not wholly disappear. Similar results appeared in the work of Booth and Maddox [9]. In contrast, the results in Fig.…”
Section: Crack Closure Behavioursupporting
confidence: 90%
“…In addition, the variation of ott/a,,, with increasing R-ratio, shows a similar general form to that of ~~~~/ c r ,~. Using u,,, the stress intensity factor range, AK,,, corresponding to the tensile stress range at the crack tip is defined as follows and an attempt is made to plot fatigue crack growth data in terms of 4, 9 4, = (urnax -%)JllaF (1) where a is crack length and F is a geometry factor. The relation between da/dN and AK,, are shown in Fig.…”
Section: Consideration On New Crack Tip Parametersmentioning
confidence: 94%
“…Theoretical loading histories 1 –3 of rolling contact fatigue exhibit mixed‐mode I and II cycles with some degree of overlap, but the ratio of the stress intensity factors changes during cycles (nonproportional loading). In addition, crack closure and locking effects 10 –13 are fundamental parameters to characterise the crack tip condition, because the normal travelling load from the wheel will compress the crack faces together, thereby inducing sliding friction. In order to have a better understanding of the growth mechanism of the squat‐like cracks, and their growth rates, we need to have a wider range of studies relating laboratory tests to rail track conditions in the field.…”
Section: Introductionmentioning
confidence: 99%
“…have observed that the d a /d N versus Δ K eff data are still considerably separate for each positive R ‐ratio, the shift of a given plot in the positive direction of the Δ K eff axis increasing with the R ‐value. Results like those presented in Refs [6–8] are likely to imply that the CC concept cannot sufficiently account for the R ‐ratio influence on crack growth. However, Toyosada and coworkers (Toyosada et al unpublished observations) did obtain a good correlation of the d a /d N versus Δ K eff data from different positive R ‐ratio tests on specimens of the same material and geometry as those used by Skorupa et al 8…”
Section: Introductionmentioning
confidence: 73%